Translation, cross-cultural adaptation, reliability, and convergent and known-group validity of the Turkish full version of the Hip Disability and Osteoarthritis Outcome Score in patients with hip osteoarthritis - Ayşenur Gökşen; Remzi Çaylak; Fatma Kübra Çekok; Turhan Kahraman (Archives of Rheumatology, 2024)
Objectives: The study aimed to culturally adapt the full version of the Hip Disability and Osteoarthritis Outcome Score (HOOS) into Turkish and evaluate its reliability and validity. Patients and methods: Patients with hip osteoarthritis were included in the methodological crosscultural adaptation study between May 2022 and December 2022. We translated and adapted the HOOS into a Turkish version and validated it in a cohort of native Turkish-speaking patients with hip osteoarthritis. The HOOS includes five subscales named symptoms, pain, activities of daily living (ADL), sport and recreation (Sport/Rec), and quality of life (QoL). The psychometric properties of the Turkish HOOS were assessed. The reliability was investigated using test-retest reliability (intraclass correlation coefficient; ICC) and internal consistency methods (Cronbach’s alpha). The convergent validity of the Turkish HOOS was evaluated by testing the predefined hypotheses using the correlations with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the European Quality of Life Scale (EQ-5D-3L), a generic QoL scale. Results: A total of 202 patients (131 females, 71 males; mean age: 55.2±9.7 years; range, 50 to 70 years) were recruited for the study. Cronbach’s alpha values for each subscale of the HOOS were as follows: symptoms=0.76, pain=0.94, ADL=0.96, Sport/Rec=0.87, QoL=0.78, and total score=0.98, indicating it has high internal consistency. For all subscales and total score of the HOOS, the ICC values were between 0.77 and 0.86, indicating good to excellent test-retest reliability. All correlations between each subscale and total score of the Turkish HOOS, WOMAC, and EQ-5D-3L were moderate to strong. Therefore, 23 predefined hypotheses out of 24 were confirmed with a confirmation rate of 96%, indicating the Turkish version of the HOOS had adequate convergent validity. Conclusion: This study shows that the Turkish version of the HOOS has a convergent and knowngroup validity, internal consistency, and test-retest reliability. It can be used to assess the patient’s perception of their hip and associated difficulties, as well as their symptoms and functional limitations.